2020
DOI: 10.1021/acs.jpca.0c10293
|View full text |Cite
|
Sign up to set email alerts
|

The Elusive Noncanonical Isomers of Ionized 9-Methyladenine and 2′-Deoxyadenosine

Abstract: Noncanonical nucleobases and nucleosides represent newly discovered species of relevance for DNA ionization. We report a targeted synthesis of gas-phase 9-methylene(1H)adenine cation radical (2 +• ) as a low-energy isomer of ionized 9methyladenine. Ion 2 +• showed unique collision-induced dissociation and UV−vis photodissociation action spectra that distinguished it from other cation radical isomers. Ab initio energy calculations with coupled cluster theory extrapolated to the complete basis set limit, CCSD(T)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“…Ab initio calculations at the CCSD­(T)/ complete basis set (CBS) level of theory have indicated that the noncanonical 2-OH methylenecytosine cation radical and its N3-H-tautomer were 59 and 56 kJ mol –1 more stable, respectively, than the canonical form . The noncanonical isomer of the 9-methyladenine cation radical, [9-methylene-( 1H )­adenine] + · , has been generated recently in the gas phase and calculated to be more stable than its canonical isomer . The [9-methylene-( 1H )­adenine] + · ion has been shown to have a distonic electronic structure, whereby the radical and charge sites resided at different atoms .…”
Section: Introductionmentioning
confidence: 99%
“…Ab initio calculations at the CCSD­(T)/ complete basis set (CBS) level of theory have indicated that the noncanonical 2-OH methylenecytosine cation radical and its N3-H-tautomer were 59 and 56 kJ mol –1 more stable, respectively, than the canonical form . The noncanonical isomer of the 9-methyladenine cation radical, [9-methylene-( 1H )­adenine] + · , has been generated recently in the gas phase and calculated to be more stable than its canonical isomer . The [9-methylene-( 1H )­adenine] + · ion has been shown to have a distonic electronic structure, whereby the radical and charge sites resided at different atoms .…”
Section: Introductionmentioning
confidence: 99%
“…The power of gas-phase ion chemistry in generating unusual DNA-related cation radicals can be illustrated by the targeted synthesis of ionized 9-methylene-(1 H ) adenine, which is the lowest-energy noncanonical isomer of 9-methyladenine cation radical (Figure ). The noncanonical isomer was found to have a distinct UV–visPD action spectrum (Figure a) that substantially differed from that of the canonical isomer (Figure b). The isomers also differed in the nature of electronic excitations giving rise to the absorption bands in the action spectra.…”
Section: Oxidative Pathways To Cation Radicals In the Gas Phasementioning
confidence: 99%
“…UV–visPD action spectra of (a) 9-methylene-(1 H )­adenine and (b) 9-methyladenine cation radicals. Adapted in part from ref . Copyright 2021 American Chemical Society.…”
Section: Oxidative Pathways To Cation Radicals In the Gas Phasementioning
confidence: 99%
See 2 more Smart Citations